Post a New Question

Math

posted by .

Simplify the expressions

(ab^2c)^-1 / a^8b^2c^-4b^3

  • Math -

    (ab^2c)^-1 = a^-1b^-2c^-1
    a^8b^2c^-4b^3 = a^8b^5c^-4
    a^-1b^-2c^-1 / a^8b^5c^-4 = a^-9b^-7c^3
    = c^3 / a^9b^7

  • Math -

    ok i get it now.

    for this question..

    3square root of 1/2x+1 +2=5

    the +2=5 is out of the square root.

    so do i get rid of the square root first or subtract 2 from 5

  • Math -

    do the reverse of PEMDAS

    3√1/(2x+1) + 2 = 5
    3/√(2x+1) = -3
    1/√(2x+1) = -1
    1 = -√(2x+1)
    squaring yields
    1 = 2x+1
    0 = 2x
    x = 0

    check:
    3/√1 + 2 = 5
    yes

    Rather a poor exercise, imho

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question